2002
DOI: 10.4049/jimmunol.169.8.4288
|View full text |Cite
|
Sign up to set email alerts
|

IL-19 Induces Production of IL-6 and TNF-α and Results in Cell Apoptosis Through TNF-α

Abstract: IL-10 is an immunosuppressive cytokine in the immune system. It was in clinical trail as an anti-inflammatory therapy for inflammatory bowel disease and various autoimmune diseases such as psoriasis, rheumatoid arthritis, and multiple sclerosis. IL-19 belongs to the IL-10 family, which includes IL-10, IL-19, IL-20, IL-22, melanoma differentiation-associated gene (MDA-7, IL-24), and AK155 (IL-26). Despite a partial homology in their amino acid sequences, they are dissimilar in their biologic functions. Little i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
235
4
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 311 publications
(261 citation statements)
references
References 24 publications
9
235
4
5
Order By: Relevance
“…A recent report from Liao et al [27] showed that in a murine system examining a non-defined population of adherent splenocytes (the majority of which are presumably macrophages), IL-19 induced TNF-a production. In our system, using peripheral blood monocytes, we did not observe induction of TNF-a by IL-19.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report from Liao et al [27] showed that in a murine system examining a non-defined population of adherent splenocytes (the majority of which are presumably macrophages), IL-19 induced TNF-a production. In our system, using peripheral blood monocytes, we did not observe induction of TNF-a by IL-19.…”
Section: Resultsmentioning
confidence: 99%
“…This IL-19 receptor is found on a number of tissues including skin, testis, ovary, heart, lung, muscle, placenta, adrenal gland, small intestine and salivary gland [26]. In a murine model of splenic adherent cell function, IL-19 has been observed to up-regulate both TNF-a and IL-6 secretion [27].…”
Section: Introductionmentioning
confidence: 99%
“…7 By using Genomatix-MatInspector software (Genomatix Software GmbH, München, Germany), 4 putative STAT6 consensus-binding sites (TTC[N]2-4GAA) were identified within the 3800-bp region upstream of the IL-19 isoform 2 transcription start site (Fig 6, A). These are as follows: STAT6-I, antisense (−) 5′ gcccTTCCagaGAAaaatc 3′ (−3251 to −3229); STAT6-II, sense (+) 5′ atttTTCTctgGAAgggct 3′ (−3250 to −3228); STAT6-III, sense (+) 5′ gcccTCCCcagGAActccc 3′ (−2259 to −2249); and the most proximal STAT6-IV, sense (+) 5′ cgatTTCCacaGAAttaga 3′ (−2163 to −2145).…”
Section: Are There Stat6-binding Cis Elements In the Promoter Region mentioning
confidence: 99%
“…2,5,6 In monocytes IL-19 secretion in response to LPS and GM-CSF has been shown to induce monocyte production of proinflammatory cytokines. 7 IL-19 expression is also upregulated in psoriatic lesions, [8][9][10] in sera from asthmatic patients, and in the urine of uremic patients, although the source of IL-19 production has not yet been identified. 11,12 Very little is known about the roles and the cellular sources of IL-19 in the lung.…”
mentioning
confidence: 99%
“…IL-19 expression showed transcriptional variants [2,61] that are detected 2-3 h after induction, indicating a feedback role in inflammation, as observed for IL-10 [2]. The secreted protein has 21% amino acid identity with IL-10 [2] and shows different levels of glycosylation [61]. IL-19 signals through IL-20R1/IL-20R2 complex [10], activating STAT3 transcription factor [62].…”
Section: Il-19mentioning
confidence: 99%